Aerobic Respiration and Its Regulation in the Metal Reducer Shewanella oneidensis - Bertling, Kristen; Banerjee, Areen; Saffarini, Daad (Frontiers in Microbiology, 2021)
Shewanella oneidensis MR-1 is a facultative anaerobe known for its ability to reduce metal oxides. Anaerobic respiration, especially metal reduction, has been the subject of extensive research. In contrast, S. oneidensis aerobic respiration has received less attention. S. oneidensis expresses cbb3- and aa3-type cytochrome c oxidases and a bd-type quinol oxidase. The aa3-type oxidase, which in other bacteria is the major oxygen reductase under oxygen replete conditions, does not appear to contribute to aerobic respiration and growth in S. oneidensis. Our results indicated that although the aa3-type oxidase does not play a role in aerobic growth on lactate, the preferred carbon source for S. oneidensis, it is involved in growth on pyruvate or acetate. These results highlight the importance of testing multiple carbon and energy sources when attempting to identify enzyme activities and mutant phenotypes. The expression of cox, cco, and cyd operons, which encode the cbb3- aa3- and bd-type oxidases, respectively, was tested in ∆crp, ∆arcA, and ∆cpdA mutants, all of which exhibit growth deficiency under aerobic conditions. The cAMP receptor protein CRP appears to positively regulate the expression of cydAB but not the cco genes. ArcA and the 3’,5’-cAMP phosphodiesterase (CpdA) did not significantly affect oxidase gene expression. Interestingly, the ∆cpdA mutant was more deficient in aerobic respiration with all carbon sources tested compared to ∆crp, which was moderately deficient only in the presence of lactate. To identify the reason for ∆cpdA aerobic growth deficiency, we isolated a suppressor mutant with transposon insertion in SO_3550. Inactivation of this gene, which encodes an anti-sigma factor, restored aerobic growth in the cpdA mutant to wild-type levels. Inactivation of SO_3550 in wild type cells, however, did not affect aerobic growth. The S. oneidensis genome encodes two additoinal CRP-like proteins that we designated CrpB and CrpC. Mutants that lack crpB and crpC were deficient in aerobic growth, but this deficiency was not due to the loss of oxidase gene expression.